Analysis Of Beginning Reading Skills Using Big Book Media For Students Of Grade III Of Sanolo Elementary School - Ramadhan, Putri; Nurwalidainismawati, Nurwalidainismawati; Wardutunnissa, Yeni (JUPE : Jurnal Pendidikan Mandala, 2025)
Early reading is a fundamental skill crucial for student success in elementary school. However, preliminary observations indicate that students' reading ability remains low due to ineffective and uninteresting learning methods. This study aims to analyze early reading skills using Big Book media for third-grade students at Sanolo Elementary School. The research method used qualitative research through a descriptive approach. The subjects in this study were 28 students. Data collection techniques included tests, observation, documentation, and interviews. Data validation techniques used triangulation of sources and methods, while data processing techniques used the four stages of Miles and Huberman: data collection, data reduction, data presentation, and conclusion drawing. The results showed that the average pretest score for students was 76.50, while the posttest score was 82.00, indicating an increase in students' early reading ability after using Big Book media. Furthermore, the use of Big Book media increased students' enthusiasm, attention, and comprehension of the reading material. In conclusion, the use of Big Book learning media is effective in improving students' reading ability and can be used as an alternative learning strategy in lower grades.